Gut Microbiome Standardization in Control and Experimental Mice. (3rd April 2017) - McCoy, Kathy D.; Geuking, Markus B.; Ronchi, Francesca
Abstract: Mouse models are used extensively to study human health and to investigate the mechanisms underlying human disease. In the past, most animal studies were performed without taking into consideration the impact of the microbiota. However, the microbiota that colonizes all body surfaces, including the gastrointestinal tract, respiratory tract, genitourinary tract, and skin, heavily impacts nearly every aspect of host physiology. When performing studies utilizing mouse models it is critical to understand that the microbiome is heavily impacted by environmental factors, including (but not limited to) food, bedding, caging, and temperature. In addition, stochastic changes in the microbiota can occur over time that also play a role in shaping microbial composition. These factors lead to massive variability in the composition of the microbiota between animal facilities and research institutions, and even within a single facility. Lack of experimental reproducibility between research groups has highlighted the necessity for rigorously controlled experimental designs in order to standardize the microbiota between control and experimental animals. Well controlled experiments are mandatory in order to reduce variability and allow correct interpretation of experimental results, not just of host‐microbiome studies but of all mouse models of human disease. The protocols presented are aimed to design experiments that control the microbiota composition between different genetic strains of experimental mice within an animal unit. © 2017 by John Wiley & Sons, Inc.